(untitled) (Journal of Environmental Science and Natural Resources, 2012)
Higher grain yield (2.45 t ha-1) was obtained in BRRI dhan34 than that of Kalizira (2.23 t ha-1). Fertilizer application @ 1.8g USG and other inorganic fertilizer ( full dose for T. aman + PM at 3.5 tha-1) gave the highest grain yield (2.85 t ha-1) and lowest grain yield (1.52 t ha-1) was found at control (no PM and NPKS). Grain yields were affected by the interaction of variety and nutrient management. The highest grain yield (2.88 t ha-1) was found in BRRI dhan34 coupled with 1.8g USG and other inorganic fertilizer(full dose for T. aman) + PM at 3.5 t ha-1 and the lowest grain yield (1.24 t ha-1) was found in Kalizira coupled with control (no PM and NPKS). The combination of fine rice BRRI dhan34 and 1.8g USG and other inorganic fertilizer (full dose for T. aman) + PM at 3.5t ha-1 appeared as the best treatment combination for the highest grain yield. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11567 J. Environ. Sci. & Natural Resources, 5(1): 129 - 132, 2012